170k views
2 votes
hich strategy would you choose to expand (x + 11)(2x + 3) and write an equivalent expression? Why? Be sure to explain your reasoning. *

User VikkyB
by
5.0k points

1 Answer

4 votes

Answer:


2x^2+25x+33

Explanation:

Given:
(x+11)(2x+3)

To expand: the given expression

Solution:

Use the formula:
(a+b)(c+d)=a(c+d)+b(c+d)

In
(x+11)(2x+3), let
a=x,b=11,c=2x,d=3

Put these values of
a,b,c,d in the formula mentioned above.

Therefore,


(x+11)(2x+3)\\=x(2x+3)+11(2x+3)\\=2x^2+3x+22x+33\\=2x^2+25x+33

So, an equivalent expression is
2x^2+25x+33

User Fazi
by
5.5k points